Thermoelectric material, thermoelectric element, thermoelectric module, device, and method for manufacturing thermoelectric material

By precipitating oxides and telluride particles, including elements such as Zn, Nb and Al, in the matrix of Bi-Te thermoelectric materials, the problem of difficult to improve the performance index Z in the prior art is solved, and high-performance thermoelectric materials are achieved , suitable for mass production and industrial applications.

CN119404622APending Publication Date: 2025-02-07KELK LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380048858.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When the existing Bi-Te thermoelectric materials improve the performance index Z, it is difficult to simultaneously increase the carrier mobility and reduce the thermal conductivity, and zinc-ante modified grain boundaries have brittleness and oxidation problems in mass production and industrial applications.

Method used

Using a thermoelectric material with the matrix composition formula A2B3, where A is Bi or Sb and B is Te, Se or S. The oxide and telluride particles are precipitated inside and at the boundary of the grains of the matrix, and elements of Zn, Nb and Al are included, through Dissolution and solidification process and sintering process preparation.

Benefits of technology

It is achieved to reduce the lattice thermal conductivity without reducing carrier mobility, thereby improving the performance index Z of thermoelectric materials, suitable for mass production and industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200686260000151
    Figure BDA0005200686260000151
  • Figure BDA0005200686260000161
    Figure BDA0005200686260000161
  • Figure HDA0005200686270000011
    Figure HDA0005200686270000011
Patent Text Reader

Abstract

The present invention relates to a thermoelectric material having a matrix represented by the compositional formula A2B3, in which A is one or more elements selected from the group consisting of Bi and Sb, and B is one or more elements selected from the group consisting of Te, Se and S. Oxide particles are deposited inside crystal grains of the matrix and / or at the boundary of the crystal grains of the matrix. The present invention relates to: a metal oxide containing one or more elements selected from the group C containing Zn, Nb, and Al; and telluride particles containing one or more elements selected from group C, the oxide particles having a long diameter of 1 nm to 1000 nm, the oxide particles having a short diameter of 1 nm to 500 nm, the telluride particles having a long diameter of 0.4 [mu] m to 40 [mu] m, and the telluride particles having a short diameter of 0.4 [mu] m to 20 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a thermoelectric material, a thermoelectric element, a thermoelectric module, a device and a method for manufacturing the thermoelectric material.

[0002] This application claims priority based on Japanese Patent Application No. 2022-104443 filed in Japan on June 29, 2022, the contents of which are incorporated herein by reference. Background Art

[0003] Conventionally, materials called Bi-Te based thermoelectric materials have been mainly used as thermoelectric materials. 2 Te 3 This means that a material having a composition in which a part or all of Bi sites of the thermoelectric material are substituted with Sb, and a part or all of Te sites are substituted with Se or S is used.

[0004] The performance index Z of thermoelectric materials is expressed as Z = α 2 σ / κ. Here α represents the Seebeck coefficient, σ represents the electrical conductivity, and κ represents the thermal conductivity. In order to improve the performance index Z of thermoelectric materials, attempts have been made to reduce the lattice thermal conductivity and increase the carrier mobility. Since thermal conductivity and Seebeck coefficient are both functions of carrier concentration, they are contradictory in most cases.

[0005] Patent document 1 proposes a thermoelectric material in which Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Nb, Mo, Y, La, Ce, Nd, Sm and Mm (mixed rare earth metals) are added to Bi-Te-based thermoelectric materials in order to promote amorphization of crystals and reduce thermal conductivity.

[0006] Non-Patent Document 1 describes that Zn is added to a p-type Bi-Te-based thermoelectric material and that segregated ZnTe contributes to a decrease in thermal conductivity.

[0007] Patent Document 2 proposes a thermoelectric material including a plurality of zinc oxide nanoparticles in a plurality of bismuth antimony telluride matrix particles of a p-type Bi—Te-based thermoelectric material and zinc-antimony modified grain boundaries between the plurality of bismuth antimony telluride matrix particles.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 3092463

[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-022731

[0012] Non-patent literature

[0013] Non-patent literature 1: Rigui Deng, et al., Energy Environ. Sci., 2018, 11, 1520 Summary of the invention

[0014] Technical problem solved by the invention

[0015] The thermoelectric material of Patent Document 1 improves the performance index by promoting amorphization. However, in general, amorphization and miniaturization of crystals in Bi-Te-based thermoelectric materials reduce thermal conductivity and carrier mobility, making it difficult to improve the performance index.

[0016] Non-patent document 1 discloses an example showing the effect of reducing the thermal conductivity of ZnTe due to segregation. In the case of a Zn-doped sample with less oxidation, the effect of reducing the thermal conductivity due to the precipitation of ZnTe is shown, but at the same time there is a problem that the carrier mobility is also reduced, and the effect of improving the performance index is insufficient.

[0017] In Patent Document 2, the mobility is improved by modifying the grain boundaries with antimony oxide. The zinc-antimony modified grain boundaries are formed in the case of a manufacturing method using a solution, such as wet chemical synthesis. The zinc-antimony modified grain boundaries are not formed in the melting method used in the mass production of conventional thermoelectric materials, so it is not suitable for mass production. In addition, due to the weak brittleness and easy oxidation properties of zinc-antimony, it is not suitable for industrial products. In Patent Document 2, zinc oxide is initially used in the form of zinc oxide during synthesis, so Zn has no reducing effect on the oxide, and contains more Sb oxides at a level that can be easily observed by X-ray diffraction (XRD). Since it is also an important cause of property degradation, it is preferably not contained in the Sb oxide.

[0018] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a thermoelectric material, a thermoelectric element, a thermoelectric module, a device, and a method for producing a thermoelectric material having an excellent performance index.

[0019] Technical means of solving problems

[0020] The thermoelectric material of one embodiment of the present invention comprises a matrix having a composition formula of A 2 B 3It means that A of the composition formula is one or more elements selected from Bi and Sb, B of the composition formula is one or more elements selected from Te, Se and S, and precipitates in at least one of the interior of the grains of the matrix and the grain boundaries of the matrix: oxide particles containing one or more elements selected from group C, the group C containing Zn, Nb and Al; and telluride particles containing one or more elements selected from group C, the major axis of the oxide particles is 1nm to 1000nm, the minor axis of the oxide particles is 1nm to 500nm, the major axis of the telluride particles is 0.4μm to 40μm, and the minor axis of the telluride particles is 0.4μm to 20μm.

[0021] Effects of the Invention

[0022] According to the above aspects of the present invention, it is possible to provide a thermoelectric material, a thermoelectric element, a thermoelectric module, a device, and a method for producing a thermoelectric material having an excellent performance index. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] [ Figure 1 ] is a flow chart of a method for manufacturing a thermoelectric material according to an embodiment of the present invention.

[0024] [ Figure 2 ] is a diagram for explaining the cutting position of the sample for measurement.

[0025] [ Figure 3 ] is a graph showing the temperature dependence of the Seebeck coefficient α of a p-type thermoelectric material prepared by powdering an ingot in air.

[0026] [ Figure 4 ] is a graph showing the temperature dependence of the resistivity ρ of a p-type thermoelectric material prepared by powdering an ingot in air.

[0027] [ Figure 5 ] is a graph showing the temperature dependence of the thermal conductivity κ of a p-type thermoelectric material prepared by powdering an ingot in air.

[0028] [ Figure 6 ] is a graph showing the temperature dependence of the performance index Z of a p-type thermoelectric material prepared by powdering an ingot in air.

[0029] [ Figure 7 ] is the weighted mobility μ of the p-type thermoelectric material obtained by converting the ingot into powder in air. w Plot of the temperature dependence of .

[0030] [ Figure 8 ] represents the lattice thermal conductivity κ of the p-type thermoelectric material prepared by turning the ingot into powder in airlat Plot of the temperature dependence of .

[0031] [ Fig. 9 ] is a graph showing the temperature dependence of the performance index Z of a p-type thermoelectric material prepared by powdering an ingot in air and a p-type thermoelectric material prepared by powdering an ingot in an inert gas atmosphere.

[0032] [ Fig.10 ] is a graph showing the temperature dependence of the quality factor (Quality factor) B of a p-type thermoelectric material prepared by powdering an ingot in air and a p-type thermoelectric material prepared by powdering an ingot in an inert gas atmosphere (in a glove box).

[0033] [ Fig.11 ] is a graph showing the distribution of the major diameters of zinc telluride particles in a p-type thermoelectric material prepared by powdering an ingot in air.

[0034] [ Fig.12 ] is a diagram showing the distribution of short diameters of zinc telluride particles in a p-type thermoelectric material prepared by powdering an ingot in air.

[0035] [ Fig.13 ] is a graph showing the distribution of the major diameters of zinc oxide particles in a p-type thermoelectric material prepared by powdering an ingot in air.

[0036] [ Fig.14 ] is a diagram showing the distribution of the short diameter of zinc oxide particles in a p-type thermoelectric material prepared by powdering an ingot in air.

[0037] [ Fig.15 ] is a diagram showing the results of Sb and O element mapping of a thermoelectric material to which Zn is not added.

[0038] [ Fig.16 ] is a graph showing the temperature dependence of thermal conductivity of a p-type thermoelectric material to which zinc oxide is added as a raw material and a p-type thermoelectric material to which zinc monomer is added as a raw material.

[0039] [ Fig.17 ] is a graph showing the dependence of the dimensionless quality factor ZT of the n-type thermoelectric material 2 at near room temperature (325K) on the ZnTe amount.

[0040] [ Fig.18 ] is a diagram showing the element distribution results of the n-type thermoelectric material 2.

[0041] [ Fig.19 ] means Bi 2 Se 0.3 Te2.7 , lattice thermal conductivity κ of n-type thermoelectric material 3 and n-type thermoelectric material 4 lat Plot of the temperature dependence of .

[0042] [ Fig. 20 ] is a graph showing the relationship between the quality factor B and the Al amount.

[0043] [ Fig.21 ] means Bi 0.45 Sb 1.55 Te 3 , a graph of the temperature dependence of the dimensionless quality factor ZT of the p-type thermoelectric material 2 and the p-type thermoelectric material 3. DETAILED DESCRIPTION

[0044] <Thermoelectric Materials>

[0045] The thermoelectric material according to an embodiment of the present invention comprises a matrix having a composition formula of A 2 B 3 Indicates that A of the composition formula is one or more elements selected from Bi and Sb, and B of the composition formula is one or more elements selected from Te, Se and S. Oxide particles containing one or more elements selected from the C group containing Zn, Nb and Al (hereinafter referred to as oxide particles containing elements of the C group), and telluride particles containing one or more elements selected from the C group (hereinafter referred to as telluride particles containing elements of the C group) are precipitated in at least one of the grain interior of the matrix and the grain boundary of the matrix. The long diameter of the oxide particles containing elements of the C group is 1nm to 1000nm, the short diameter of the oxide particles containing elements of the C group is 1nm to 500nm, the long diameter of the telluride particles containing elements of the C group is 0.4μm to 40μm, and the short diameter of the telluride particles containing elements of the C group is 0.4μm to 20μm. The thermoelectric material of this embodiment can be used for both n-type semiconductors and p-type semiconductors. It should be noted that in this specification, the numerical range represented by "to" means that the numerical values ​​recorded before and after "to" are set as the lower limit and the upper limit and the range is included. The numerical values ​​represented by "lower than" or "exceed" are not included in the numerical range. Hereinafter, each element is described.

[0046] <Base>

[0047] The composition formula of the thermoelectric material of this embodiment is A 2 B 3In other words, A in the composition formula is one or more elements selected from Bi and Sb (hereinafter referred to as elements of group A), and B in the composition formula is one or more elements selected from Te, Se and S (hereinafter referred to as elements of group B). The ratio of the total number of atoms of the elements of group A to the total number of atoms of the elements of group B (elements of group A: elements of group B) is 2:3. As a matrix, for example, Bi 2 Te 3 , Sb 2 Te 3 、Bi 2 Se 3 , Sb 2 Se 3 、Bi 2 S 3 , Sb 2 S 3 、Bi 0.46 Sb 1.54 Te 3 、(Bi 0.225 Sb 0.775 ) 2 Te 3 Etc. The matrix preferably contains Te.

[0048] When the thermoelectric material of the embodiment is used as an n-type semiconductor, it is preferable to increase the ratio of Se and S in the elements of group B in the matrix. Specifically, it is preferable to set the atomic ratio of Se and S to Te in the matrix ((Se+S) / (Te+Se+S)) to 0 to 0.33.

[0049] When the thermoelectric material of the embodiment is used as a p-type semiconductor, it is preferable to increase the ratio of Sb in the matrix among the elements of group A. Specifically, it is preferable to set the atomic ratio of Bi to Sb (Bi / (Sb+Bi)) in the matrix to 0 to 0.30.

[0050] When the thermoelectric material of the embodiment is used as an n-type semiconductor, it preferably contains a halogen element such as Cl, Se, or I. The content of the halogen element is preferably 0.030 at% to 0.20 at% relative to the entire matrix. The content of the halogen element is more preferably 0.050 at% to 0.12 at%.

[0051] When the thermoelectric material of the embodiment is used as a p-type semiconductor, the matrix may contain a 14th group element such as Ge, Sn, or Pb. The content of the 14th group element is preferably 0 at% to 0.20 at% relative to the entire matrix. The content of the 14th group element is more preferably 0 at% to 0.15 at%. The at% of each element can be analyzed, for example, by an inductively coupled plasma mass spectrometer (ICP-MS).

[0052] The matrix of the thermoelectric material of the embodiment is preferably polycrystalline, and more preferably no halo pattern derived from an amorphous phase is observed by X-ray diffraction.

[0053] <Oxide Particles Containing Group C Element>

[0054] In the thermoelectric material of the embodiment, oxide particles of elements of group C containing one or more selected from Zn, Nb and Al are precipitated in at least one of the grain interior of the matrix and the grain boundary of the matrix. In the thermoelectric material of the embodiment, the oxide particles containing elements of group C preferably contain at least Zn. In addition, in the thermoelectric material of the embodiment, the oxide particles containing elements of group C preferably contain at least Nb. In the thermoelectric material of the embodiment, the oxide particles containing elements of group C preferably contain at least Al. In the thermoelectric material of the embodiment, the oxide particles containing elements of group C particularly preferably contain at least Zn. The oxide particles containing elements of group C are, for example, zinc oxide (ZnO) particles. In the thermoelectric material of the embodiment, the number of oxide particles containing elements of group C is preferably greater than the number of telluride particles containing elements of group C. The number of oxide particles containing elements of group C is preferably greater than the number of particles of monomers of elements of group C.

[0055] The long diameter of the oxide particles containing elements of group C is 1nm to 1000nm. The long diameter of the oxide particles containing elements of group C is preferably 20nm to 480nm. The long diameter of the oxide particles containing elements of group C is more preferably 20nm to 350nm. It should be noted that more than 75% of the oxide particles containing elements of group C satisfy the numerical range of the long diameter. More preferably, more than 80% of the oxide particles containing elements of group C satisfy the numerical range of the long diameter. It is further preferred that more than 90% of the oxide particles containing elements of group C satisfy the numerical range of the long diameter.

[0056] The short diameter of the oxide particles containing elements of group C is 1nm to 500nm. The short diameter of the oxide particles containing elements of group C is preferably 10nm to 260nm. The short diameter of the oxide particles containing elements of group C is more preferably 10nm to 190nm. It should be noted that more than 75% of the oxide particles containing elements of group C satisfy the numerical range of the short diameter. More preferably, more than 80% of the oxide particles containing elements of group C satisfy the numerical range of the short diameter. It is further preferred that more than 90% of the oxide particles containing elements of group C satisfy the numerical range of the short diameter.

[0057] <Telluride particles containing an element of Group C>

[0058] In the thermoelectric material of the embodiment, telluride particles containing one or more elements of group C selected from Zn, Nb and Al are precipitated in at least one of the crystal grains of the matrix and the crystal grain boundaries of the matrix. The elements of group C are not easily substituted for A. 2 B 3 The A and B sites in the 2 B 3 The element that can be intercalated between the crystal lattices of the element without significantly changing the carrier concentration, and is an element with a higher ionization tendency than the elements of the A group and the elements of the B group. The elements of the C group are elements that have a higher ionization tendency than the elements of the A group and the elements of the B group, and therefore function as an oxygen absorbing gas absorber. In the thermoelectric material of the embodiment, the telluride particles containing the elements of the C group preferably contain at least Zn. In addition, in the thermoelectric material of the embodiment, the telluride particles containing the elements of the C group preferably contain at least Nb. In the thermoelectric material of the embodiment, the telluride particles containing the elements of the C group preferably contain at least Al. In the thermoelectric material of the embodiment, the telluride particles containing the elements of the C group particularly preferably contain at least Zn. The telluride particles are, for example, zinc telluride (ZnTe) particles. It should be noted that at least one of the oxide particles containing the elements of the C group and the telluride particles containing the elements of the C group may contain at least Zn. At least one of the oxide particles containing the elements of the C group and the telluride particles containing the elements of the C group may contain at least Nb. At least one of the oxide particles including the element of group C and the telluride particles including the element of group C may include at least Al.

[0059] The long diameter of the telluride particles containing elements of group C is 0.4 μm to 40 μm. The long diameter of the telluride particles containing elements of group C is preferably 0.6 μm to 21 μm. The long diameter of the telluride particles containing elements of group C is more preferably 0.6 μm to 15 μm. It should be noted that more than 75% of the telluride particles containing elements of group C satisfy the numerical range of the long diameter. More preferably, more than 80% of the telluride particles containing elements of group C satisfy the numerical range of the long diameter. It is further preferred that more than 90% of the telluride particles containing elements of group C satisfy the numerical range of the long diameter.

[0060] The short diameter of the telluride particles containing elements of group C is 0.4 μm to 20 μm. The short diameter of the telluride particles containing elements of group C is preferably 0.4 μm to 10.5 μm. The short diameter of the telluride particles containing elements of group C is more preferably 0.4 μm to 7.5 μm. It should be noted that more than 75% of the telluride particles containing elements of group C satisfy the numerical range of the short diameter. More preferably, more than 80% of the telluride particles containing elements of group C satisfy the numerical range of the short diameter. It is further preferred that more than 90% of the telluride particles containing elements of group C satisfy the numerical range of the short diameter.

[0061] <Method for measuring the major axis and minor axis of oxide particles containing elements of group C and telluride particles containing elements of group C>

[0062] The major axis and minor axis of oxide particles containing elements of Group C and telluride particles containing elements of Group C can be measured, for example, by the following method. For example, a thermoelectric material is processed by ion milling, focused ion beam (FIB), etc. to obtain a sample for cross-sectional observation. For the obtained sample for cross-sectional observation, cross-sectional observation is performed by a transmission electron microscope (TEM) or a scanning electron microscope (SEM) to obtain a cross-sectional image. It should be noted that, in cross-sectional observation, for example, an energy-dispersive X-ray spectrometer (EDS) attached to a TEM, etc. is used to perform elemental distribution. In elemental distribution, particles in which elements of Group C and oxygen are detected are regarded as oxide particles containing elements of Group C, and particles in which elements of Group C and Te are detected are regarded as telluride particles containing elements of Group C. Particles in which only elements of Group C are detected are regarded as particles of elemental monomers of Group C. For the obtained elemental mapping images, image analysis software such as ImageJ Fiji, etc. is used to set a threshold (for example, excluding 5.94% on the background side of the concentration distribution histogram at the time of binarization, etc.) in such a way that the contours of the oxide particles and telluride particles become clear, and image processing is performed. The major axis and minor axis of oxide particles containing elements of Group C and telluride particles containing elements of Group C can be obtained by performing elliptical approximation processing on the obtained oxide particles and telluride particles. In the case where the measured particles are spherical, elliptical processing is performed in the same manner. It should be noted that 8 fields of view are observed for oxide particles containing elements of Group C (for example, measurement field of view: 3.3 μm × 3.3 μm), and 4 fields of view are observed for telluride particles containing elements of Group C (for example, measurement field of view: 414 μm × 285 μm), and their ranges are evaluated based on the major axis and minor axis of oxide particles containing elements of Group C and the major axis and minor axis of telluride particles containing elements of Group C obtained from each distribution image.

[0063] <Content of Zn>

[0064] Relative to the entire thermoelectric material, the Zn content of the thermoelectric material of the embodiment is preferably 0.40 to 2.3 at%. The Zn content is more preferably 0.40 to 1.2 at%. Further preferably, it is 0.79 to 1.2 at%. The content of Zn in the thermoelectric material of the embodiment can be measured, for example, by an inductively coupled plasma mass spectrometer (ICP-MS). It should be noted that the numerical value of the content is rounded to 2 digits.

[0065] <Content of Al>

[0066] Relative to the overall thermoelectric material, the content of Al in the embodiment is preferably 1.99 to 3.97 at%. The content of Zn in the thermoelectric material of the embodiment can be measured, for example, by an Inductively Coupled Plasma Mass Spectrometer (ICP-MS). It should be noted that the numerical value of the content is rounded to 3 digits.

[0067] <Sb oxide>

[0068] In the thermoelectric material of the embodiment, the maximum value of the number density of Sb oxide particles is preferably 31.2 particles / μm 2 Hereinafter. The maximum value of the number density of Sb oxide particles is more preferably 12.4 particles / μm 2 Hereinafter. The maximum value of the number density of Sb oxide particles is further preferably 1.6 particles / μm 2 Hereinafter. Sb oxide is preferably less, so the lower limit of the number density of Sb oxide particles is 0 particles / mm 2 The Sb oxide is, for example, Sb 2 O 3 .

[0069] <Bi oxide>

[0070] In the thermoelectric material of the embodiment, the maximum value of the number density of Bi oxide particles is preferably 31.2 particles / μm 2 Hereinafter. The maximum value of the number density of Bi oxide particles is more preferably 12.4 particles / μm 2 Hereinafter. The maximum value of the number density of Bi oxide particles is further preferably 1.6 particles / μm 2 Hereinafter. Sb oxide is preferably less, so the lower limit of the maximum value of the number density of Bi oxide particles is 0 particles / mm 2 The Bi oxide is, for example, Bi 2 O 3 .

[0071] <Method for measuring the number density of Sb oxide particles and Bi oxide particles>

[0072] The number density of Sb oxide particles and Bi oxide particles can be measured, for example, by the following method. The thermoelectric material is processed by, for example, a focused ion beam (FIB) to obtain a sample for cross-sectional observation. The obtained sample for cross-sectional observation is observed by a transmission electron microscope (TEM) to obtain a cross-sectional image. In the cross-sectional observation, element distribution is performed, for example, by an energy dispersive X-ray spectrometer attached to a TEM, and particles in which Sb and oxygen are detected are determined to be Sb oxide particles, and particles in which Bi and oxygen are detected are determined to be Bi oxide particles. An 8-field observation is performed (for example, a measurement field: 3.3 μm×3.3 μm), and the number density of Sb oxide particles and the number density of Bi oxide particles are calculated from the number of Sb oxide particles obtained from the cross-sectional image, the number of Bi oxide particles, and the area of ​​the measurement field. The maximum value of the number density of Sb oxide particles in each field of view obtained by the measurement of 8 fields of view is taken as the maximum value of the number density of Sb oxide particles. The maximum value of the number density of Bi oxide particles in each field of view obtained by the measurement of 8 fields of view is taken as the maximum value of the number density of Bi oxide particles.

[0073] <Oxygen concentration>

[0074] The oxygen concentration of the thermoelectric material of the embodiment is preferably 100 ppm or more. The oxygen concentration is more preferably 400 ppm or more. The oxygen concentration is further preferably 1000 ppm or more. The oxygen concentration of the thermoelectric material can be measured by, for example, inert gas fusion-non-dispersive infrared absorption method (NDIR).

[0075] The thermoelectric material of the embodiment has been described above. The thermoelectric material of the embodiment can be used in a thermoelectric element. In addition, the thermoelectric element can be used in a thermoelectric module. Furthermore, the thermoelectric module can be used in equipment such as a precision temperature control device and a power generation device.

[0076] <Effects>

[0077] The thermoelectric material of the embodiment precipitates oxide particles (long diameter: 1nm to 1000nm, short diameter: 1nm to 500nm) containing elements of the C group in at least one of the grain interior of the matrix and the grain boundary of the matrix, so that the lattice thermal conductivity can be reduced without reducing the carrier mobility. Thus, the performance index Z of the thermoelectric material of the embodiment can be improved.

[0078] The thermoelectric material of the embodiment precipitates telluride particles (long diameter: 0.4 μm to 40 μm, short diameter: 0.4 μm to 20 μm) containing elements of group C in at least one of the crystal grains of the matrix and the crystal grain boundaries of the matrix, thereby reducing the lattice thermal conductivity. Thus, the performance index Z of the thermoelectric material of the embodiment can be improved.

[0079] In the thermoelectric material of the embodiment, the performance index Z of the thermoelectric material of the embodiment can be further improved by increasing the number of oxide particles containing an element of the C group relative to the number of telluride particles containing an element of the C group.

[0080] By setting the number density of the Sb oxide particles and the Bi oxide particles of the embodiment to 31.2 particles / μm 2 Next, the carrier mobility of the thermoelectric material of the embodiment is further improved.

[0081] When the oxygen concentration of the thermoelectric material of the embodiment is 1000 ppm or more, an appropriate number of oxide particles containing an element of group C can be formed, and the performance index Z can be further improved.

[0082] <Method for producing thermoelectric material>

[0083] Next, a method for producing a thermoelectric material according to an embodiment will be described. The production method described below is an example of a method for producing a thermoelectric material according to an embodiment, and the present invention is not limited to the following production method. Figure 1 This is a flowchart of a method for producing a thermoelectric material according to an embodiment. The method for producing a thermoelectric material according to an embodiment comprises: a dissolution and solidification step S1 of dissolving and solidifying a raw material to obtain a solidified product, wherein the raw material contains an element of Group A that is at least one selected from Bi and Sb, an element of Group B that is at least one selected from Te, Se and S, and an element of Group C that is at least one selected from Zn, Nb and Al; a powder preparation step S2 of obtaining a powder from the solidified product; and a sintering step S3 of sintering the powder. In the dissolution and solidification step S1, at least a part of one or more elements selected from Group C in the raw material exists as a monomer. Each step is described below.

[0084] <Dissolution and Solidification Process>

[0085] In the dissolution and solidification step S1, a raw material containing at least one element selected from the A group including Bi and Sb; at least one element selected from the B group including Te, Se and S; and at least one element selected from the C group including Zn, Nb and Al is dissolved and solidified.

[0086] <Raw Materials>

[0087] The raw material contains: at least one element selected from the group A including Bi and Sb; at least one element selected from the group B including Te, Se and S; and at least one element selected from the group C including Zn, Nb and Al. For example, the raw material may be a telluride containing an element of the group C in an amount of 100% and the remainder may be a composition formula A 2 B 3The atomic ratio of each element is determined by the method of expressing the matrix. Here, y in yat% refers to the atomic concentration of the telluride containing the element of group C relative to the total atoms in the raw material. Here, A in the composition formula refers to at least one element selected from Bi and Sb. In addition, B in the composition formula refers to at least one element selected from Te, Se and S. The telluride containing the element of group C is ZnTe, Al 2 Te 3 、NbTe 2 , Nb 3 Te 4 、NbTe 4 Etc. It should be noted that the telluride containing the element of group C does not need to be contained as a telluride, and the element of group C and Te can be contained in the raw material as monomers. In the present embodiment, at least a part of the element of group C in the raw material exists as a monomer. The element of group C is preferably contained in the raw material as a monomer. Each element is preferably uniformly mixed in the raw material. In addition, the raw material may contain the halogen elements, group 14 elements, etc. as exemplified above.

[0088] <Heating temperature>

[0089] In the dissolving and solidifying step S1, the raw material is heated in a vacuum or in an inert gas at a heating temperature of at least the melting point of the raw material and not more than 1000°C. More preferably, the raw material is heated in a range of 650°C to 850°C. The heating temperature at this time is, for example, the set temperature of the heating furnace. By heating the raw material in a range of 650°C to 850°C, each element in the raw material can be dissolved.

[0090] <Heating time>

[0091] The raw material is heated at the heating temperature for a certain time. The heating time is not particularly limited as long as the raw material is completely melted. For example, the heating time is 1 hour to 60 hours.

[0092] <Heating rate>

[0093] In the dissolving and solidifying step S1, the average heating rate when heating from room temperature (eg, 20°C to 30°C) to the heating temperature is preferably, for example, 1°C / min to 20°C / min. In order to suppress oxidation of the raw material, the raw material is preferably heated in a vacuum or in an inert gas.

[0094] <Cooling speed>

[0095] In the dissolution and solidification step S1, the raw material is heated for a certain period of time and then cooled from the heating temperature to room temperature to obtain a solidified product. The average cooling rate when cooling from the heating temperature to room temperature is preferably, for example, 0.1°C / min to 20°C / min.

[0096] <Powder Preparation Process>

[0097] In the powder preparation step S2, powder is obtained from the solidified material obtained by the dissolution solidification step. Bubbles sometimes remain in the solidified material, and sometimes elements are segregated. Therefore, the solidified material is made into powder. At this time, it is preferred to pulverize the solidified material in the air or expose the prepared powder to the air.

[0098] The method for preparing the powder is not particularly limited and examples of the method include pulverization using a mortar, a stirrer, a ball mill, etc., an atomization method, and a single roll method (meltspun method).

[0099] <Sintering process>

[0100] In the sintering step S3, the powder obtained in the powder preparation step S2 is sintered to obtain a thermoelectric material. The sintering method is not particularly limited. As the sintering method, for example, hot press sintering or pulsed electric current sintering (PECS) can be cited. In pulsed electric current sintering, the temperature can be rapidly raised to the target temperature.

[0101] The sintering temperature, sintering pressure, and sintering time are not particularly limited as long as the target thermoelectric material can be obtained. For example, the sintering temperature is preferably 350° C. to 550° C. In addition, the sintering pressure is preferably, for example, 10 MPa to 90 MPa. And, the sintering time is preferably, for example, 1 minute to 120 minutes.

[0102] The atmosphere during sintering is not particularly limited as long as the target thermoelectric material can be obtained, but a vacuum or inert gas atmosphere is preferred in order to suppress oxidation during sintering.

[0103] <Effects>

[0104] In the past, zinc oxide powder was mostly added at the stage before synthesis. In this case, the particle size of the original zinc oxide powder will not be reduced to less than that of the original zinc oxide powder. In addition, zinc oxide has a small specific gravity and a high melting point, so it will not dissolve or disperse in the matrix and will remain separated at the bottom of the glass tube or quartz tube, or the powders will condense with each other, so it is difficult to evenly disperse the zinc oxide particles.

[0105] On the other hand, the manufacturing method of the thermoelectric material of this embodiment can precipitate and disperse zinc oxide nanoparticles by adding elements of group C such as zinc and Te to the raw material in a surplus manner. In this case, tellurides containing elements of group C are also precipitated, which can help reduce thermal conductivity and improve performance index.

[0106] The thermoelectric material of the embodiment can function as a getter material that absorbs oxygen by causing at least a portion of the elements of group C in the raw material to exist as a single substance. Thus, the maximum value of the number density of Sb oxide particles and Bi oxide particles can be 31.2 particles / μm. 2 As a result, the performance index Z of the thermoelectric material can be further improved.

[0107] In the powder preparation step S2, oxidation can be actively promoted by crushing the solidified material in the air or exposing it to the air. As a result, the oxygen concentration in the thermoelectric material can be made to be 1000 ppm or more. By making the oxygen concentration in the thermoelectric material 1000 ppm or more and forming an appropriate number of oxide particles containing elements of the C group, the performance index Z can be further improved.

[0108] As mentioned above, although embodiment of this invention is described, this invention is not limited to this, It can change suitably within the range which does not deviate from the technical idea of ​​the said invention.

[0109] Example

[0110] Next, the embodiments of the present invention are described. The conditions of the embodiments are examples of conditions used to confirm the feasibility and effect of the present invention. The present invention is not limited to the examples of the conditions. The present invention can adopt various conditions as long as they do not deviate from the main purpose of the present invention and achieve the purpose of the present invention.

[0111] <Details of Example>

[0112] According to the composition, raw materials containing each element of Bi, Sb, Te, Se, Zn, and Al are sealed in a quartz or PYREX (registered trademark) glass tube and heated at a temperature lower than the melting point of the alloy (Bi 2 Te 3 The melting point of Sb is 588.5℃. 2 Te 3 The melting point of Zn is 618.5°C) and the melting point is 650°C or higher and 1000°C or lower. The melting point is 618.5°C ... 2 Se 0.3 Te 2.7 and Bi 0.45 Sb 1.55 Te 3 It should be noted that the following (Bi x Sb 1-x ) 2 Te 3+y at% ZnTe means, relative to (Bi x Sb 1-x ) 2 Te 3 1 mol, ZnTe is y / 100 mol. 0.45 Sb 1.55 Te 3 +y at%AlTe means, relative to Bi 0.45 Sb 1.55 Te 3 1 mol, AlTe is y / 100 mol. Bi 0.45 Sb 1.55 Te 3 +y at %Al 2 Te 3 It means that relative to Bi 0.45 Sb 1.55 Te 3 1 mol, Al 2 Te 3 is y / 100 mol. Similarly, Bi 2 (Te 0.9 Se 0.1 ) 3 +yat% ZnTe means, relative to Bi 2 (Te 0.9 Se 0.1 ) 3 1 mol, ZnTe is y / 100 mol. 2 Se 0.3 Te 2.7 +y at% ZnTe means, relative to Bi 2 Se 0.3 Te 2.7 1 mol, ZnTe is y / 100 mol. BiI 3 It is added in combination to adjust the carrier concentration and has no direct effect on improving thermoelectric performance. 2 Se 0.3 Te 2.7 +y at%AlTe means, relative to Bi 2 Se 0.3 Te 2.7 1 mol, AlTe is y / 100 mol. 2 Se 0.3 Te 2.7 +y at %Al 2 Te 3 It means that relative to Bi 2 Se 0.3 Te 2.7 1 mol, Al2 Te 3 is y / 100 mol.

[0113] p-type thermoelectric material 1: (Bi x Sb 1-x ) 2 Te 3 +y at%ZnTe(x=0.2, 0.225, y=0, 2, 4, 6, 12)

[0114] p-type thermoelectric material 2: Bi 0.45 Sb 1.55 Te 3 +y at%AlTe(y=4)

[0115] p-type thermoelectric material 3: Bi 0.45 Sb 1.55 Te 3 +y at %Al 2 Te 3 (y=2)

[0116] n-type thermoelectric material 1: Bi 2 (Te 0.9 Se 0.1 ) 3 +y at% ZnTe (y = 0, 2, 4)

[0117] n-type thermoelectric material 2: Bi 2 Se 0.3 Te 2.7 +y at% ZnTe + 0.08wt% BiI 3 (y=0、2、4)

[0118] n-type thermoelectric material 3: Bi 2 Se 0.3 Te 2.7 +y at%AlTe(y=2)

[0119] n-type thermoelectric material 4: Bi 2 Se 0.3 Te 2.7 +y at %Al 2 Te 3 (y=0.5)

[0120] Next, the ingot is processed into powder in air or in an inert gas (in a glove box), and a sintered body (thermoelectric material) is prepared using a sintering device in an inert gas. Assuming that the current and heat flow in the pressurized direction of the sintered body or in a direction perpendicular to it, Figure 2 As shown, a sample for measuring the Seebeck coefficient and the electrical resistance and a sample for measuring the thermal conductivity were cut out from the sintered body.

[0121] <Seebeck coefficient and resistivity>

[0122] Regarding the measurement of the Seebeck coefficient and resistivity, samples for Seebeck coefficient and resistance measurement were measured using a thermoelectric property evaluation device (ZEM-3M8) manufactured by ADVANCE RIKO in the temperature range from room temperature to 250 °C.

[0123] <Measurement of the major axis and minor axis of zinc oxide particles and zinc telluride particles>

[0124] Each thermoelectric material was processed by Ar ion milling to obtain a sample for cross-sectional observation. The samples for cross-sectional observation obtained by TEM or SEM were subjected to elemental distribution by EDS. Particles detected with zinc and oxygen were regarded as oxide particles containing elements of Group C (zinc oxide particles), and particles detected with zinc and Te were regarded as telluride particles containing elements of Group C (zinc telluride particles). For the obtained elemental mapping images, image analysis software ImageJ Fiji was used to set a threshold (except for 5.94% on the background side of the concentration distribution histogram during binarization, etc.) in such a way that the contours of the oxide particles and telluride particles became clear, and image processing was performed. By performing elliptical approximation processing on the obtained oxide particles and telluride particles, the major axis and minor axis of the oxide particles containing elements of Group C and the telluride particles containing elements of Group C were obtained. It should be noted that 8 fields of view were observed for the oxide particles (measurement field of view: 3.3 μm × 3.3 μm), and 4 fields of view were observed for the telluride particles (measurement field of view: 414 μm × 285 μm). Based on the major axis and minor axis of the oxide particles containing elements of Group C and the major axis and minor axis of the telluride particles containing elements of Group C obtained from each cross-sectional image, their ranges were evaluated.

[0125] <Measurement of the number density of Sb oxide particles and Bi oxide particles>

[0126] Each thermoelectric material was processed by focused ion beam (FIB) to obtain a sample for cross-sectional observation. The samples for cross-sectional observation obtained by TEM were subjected to elemental distribution by EDS. Particles detected with Sb and oxygen were determined as Sb oxide particles, and particles detected with Bi and oxygen were determined as Bi oxide particles. 8 fields of view were observed (measurement field of view: 3.3 μm × 3.3 μm). From the number of Sb oxide particles obtained from each cross-sectional image and the area of its measurement field of view, the number density of Sb oxide particles in each field of view was calculated. Among the obtained number densities, the maximum value was taken as the maximum value of the number density.

[0127] <Thermal conductivity>

[0128] The thermal conductivity was measured in a temperature range from room temperature to 250° C. using a laser flash apparatus (LFA 467 HyperFlash) manufactured by Netsch.

[0129] <Oxygen concentration>

[0130] The oxygen concentration of the thermoelectric material prepared as described above was measured using an oxygen / nitrogen analyzer EMGA-920 manufactured by HORIBA Mfg. Co., Ltd.

[0131] Figure 3 2 shows the temperature dependence of the Seebeck coefficient α of a p-type thermoelectric material prepared by powdering an ingot in air. Figure 3 The horizontal axis is temperature (℃), Figure 3 The vertical axis is the Seebeck coefficient α (μV / K). Figure 4 ] The temperature dependence of the resistivity ρ of a p-type thermoelectric material prepared by powdering an ingot in air is shown in FIG. Figure 4 The horizontal axis is temperature (℃), Figure 4 The vertical axis is the resistivity ρ (μΩ·cm). Figure 5 2 shows the temperature dependence of the thermal conductivity κ of a p-type thermoelectric material prepared by powdering an ingot in air. Figure 5 The horizontal axis is temperature (℃), Figure 5 The vertical axis is thermal conductivity κ (mW / (cm·K)). Figure 6 ] The temperature dependence of the performance index Z of a p-type thermoelectric material prepared by powdering an ingot in air is shown in FIG. Figure 6 The horizontal axis is temperature (℃), Figure 6 The vertical axis is the performance index Z (10 -3 / K).

[0132] Figure 3 to Figure 6 The result is that relative to the preparation value (Bi 0.225 Sb 0.775 ) 2 Te 3 The stoichiometric composition of Zn and Te is changed in the amount of Zn and Te added (0 to 12 at%) so that Zn and Te are in excess at a ratio of 1:1. Specifically, (Bi 0.225 Sb 0.775 ) 2 Te 3 +y at% ZnTe is relative to (Bi 0.225 Sb 0.775x ) 2 Te 31 mol, ZnTe is y / 100 mol (y: 0-12). For example, when ZnTe is 2 at%, the Zn content is 0.40 at% relative to the whole thermoelectric material. When ZnTe is 4 at%, the Zn content is 0.79 at% relative to the whole thermoelectric material. Similarly, when ZnTe is 6 at%, the Zn content is 1.2 at% relative to the whole thermoelectric material. When ZnTe is 12 at%, the Zn content is 2.3 at% relative to the whole thermoelectric material.

[0133] Figure 3 to Figure 6 As shown in the measurement results, even if the amount of excess ZnTe added increases, the Seebeck coefficient α hardly changes, so it can be seen that the carrier concentration in any sample is the same. On the other hand, when the amount of excess ZnTe added increases, the resistivity ρ and thermal conductivity κ are the smallest when y = 4at% or 6at%. The performance index Z as a function of the Seebeck coefficient α, resistivity ρ, and thermal conductivity κ is the largest when y = 4at%.

[0134] Seebeck coefficient α, resistivity ρ, and thermal conductivity κ are all functions of carrier concentration. Resistivity ρ and thermal conductivity κ in Bi-Te thermoelectric materials vary greatly depending on crystal orientation and scattering sources, so it is difficult to identify the main cause of the change unless the carrier concentration is kept constant. On the other hand, the absolute value of Seebeck coefficient α is less affected by crystal orientation and scattering sources, and shows roughly the same value when the carrier concentration is the same.

[0135] for Figure 3 to Figure 6 The results more strictly exclude the influence of carrier concentration. Therefore, the weighted mobility μw expressed by the following formula (1) and the lattice thermal conductivity κlat expressed by the following formula (2) and (3) are used to compare the characteristics of the samples. In the following formula (1), h is Planck's constant, σ is conductivity, e is elementary charge, and m is e is the mass of the electron, k B is the Boltzmann constant, T is the absolute temperature, and α is the Seebeck coefficient. In the following equations (2) and (3), κ el is the electronic thermal conductivity, L is the Lorentz number, T is the absolute temperature, and σ is the electrical conductivity. These values ​​are the values ​​corresponding to the mobility without the influence of the carrier concentration, and the thermal conductivity without the heat conduction due to the carriers.

[0136] [Mathematical formula 1]

[0137]

[0138] κ lat =κ-κ el …(2)

[0139] κ el=LTσ…(3)

[0140] Figure 7 where μ represents the weighted mobility w temperature dependence. Figure 7 The horizontal axis is temperature (℃), and the vertical axis is μ w (cm 2 / (V·s)). Figure 8 where κ represents the lattice thermal conductivity lat temperature dependence. Figure 8 The horizontal axis is temperature (℃), and the vertical axis is κ lat (mW / (cm·K)). Figure 3 to Figure 6 Similarly, μ w It is the largest at y = 6 at%, and κlat is the smallest at y = 4. In any case, when Te and Zn as a C group element are excessively added compared to y = 0, better characteristics are achieved.

[0141] Next, a comparison was made between the case where the ingot was pulverized in air to produce powder and the case where the ingot was pulverized in an inert gas atmosphere. Fig. 9 ] The temperature dependence of the performance index Z of a p-type thermoelectric material prepared by powdering an ingot in air and a p-type thermoelectric material prepared by powdering an ingot in an inert gas atmosphere (in a glove box) is shown in FIG. Fig. 9 The horizontal axis is temperature (℃), and the vertical axis is performance index Z (10 -3 / K). In addition, Fig.10 Graph (A) shows the temperature dependence of the quality factor B of a p-type thermoelectric material prepared by powdering an ingot in air and a p-type thermoelectric material prepared by powdering an ingot in an inert gas atmosphere (in a glove box). Fig.10 The horizontal axis is the amount of ZnTe added (at%), and the vertical axis is the quality factor B. The quality factor B is shown in the following formula (4). In the following formula (4), h is Planck's constant, e is the basic charge, and m is e is the mass of the electron, k B is the Boltzmann constant, T is the absolute temperature, μ w is the weighted mobility, κ lat is the lattice thermal conductivity.

[0142] [Mathematical formula 2]

[0143]

[0144] like Fig. 9 As shown in Figure 2, the performance index of the thermoelectric material is higher when the powder is pulverized in air than when it is pulverized in an inert gas atmosphere. Fig.10As shown, when the material is pulverized in air, the quality factor B is the largest when the concentration of ZnTe is 4 at%, and in an inert gas atmosphere, the more ZnTe is added, the lower the quality factor B is. From these results, it can be seen that adding ZnTe and introducing oxygen can further improve the performance index. When the oxygen concentration of the thermoelectric material (without adding Zn, y = 0 at%) manufactured under the same conditions as these samples was measured, the result was 431 ppm when pulverized in a glove box and 1150 ppm when pulverized in air. The oxygen concentration is estimated to be the same when ZnTe is added.

[0145] Next, the observation results of the crystal structure are described. The results of SEM observation of a p-type sample to which Zn and Te (6 at%) were excessively added confirmed that segregated particles of zinc telluride (ZnTe) with a long diameter of 0.4 to 40 μm and a short diameter of 0.4 to 20 μm were precipitated in at least one of the grain interior of the matrix and the grain boundary of the matrix. The distribution of the long diameter and the short diameter of the zinc telluride particles obtained by SEM and EDS are shown in Figure 1. Fig.11 and Fig.12 shown. Fig.11 It shows the distribution of the major diameter of zinc telluride particles. Fig.11 The horizontal axis represents the particle size (μm), and the vertical axis represents the frequency (number). Fig.12 The graph shows the distribution of the short diameter of zinc telluride particles. Fig.12 The horizontal axis represents the particle size (μm), and the vertical axis represents the frequency (number). Fig.11 and Fig.12 As shown, 90% or more of the telluride particles have a major axis of 0.4 μm to 40 μm and a minor axis of 0.4 μm to 20 μm.

[0146] For the thermoelectric material in which zinc telluride was observed, the major axis and minor axis of the zinc oxide particles were measured by STEM-EDS. It should be noted that the zinc oxide particles were precipitated in at least one of the grain interior of the matrix and the grain boundary of the matrix. The results obtained are as follows: Fig.13 and Fig.14 shown. Fig.13 It shows the distribution of the major diameter of zinc oxide particles. Fig.13 The horizontal axis represents the particle size (μm). Fig.13 The vertical axis represents frequency (number). Fig.14 It shows the distribution of the minor diameter of zinc oxide particles. Fig.14 The horizontal axis represents the particle size (μm), and the vertical axis represents the frequency (number). Fig.13 and Figure 4The horizontal axis [x, y] indicates that the particle size is greater than x and less than y. More than 90% of the zinc oxide particles have a long diameter of 1 nm to 1000 nm and a short diameter of 1 nm to 500 nm. A large amount of zinc oxide was confirmed, but no Sb oxide particles were confirmed (number density 0 particles / mm 2 ) In addition, the number of Zn simple substance particles is 0, and the number of zinc oxide particles is large.

[0147] The results of the element distribution of Sb without Zn addition are as follows: Fig.15 (a) shows the element distribution of O. Fig.15 (b) As shown. In the thermoelectric material without Zn addition, Fig.15 As shown in FIG. 1 , a large number of Sb oxide particles were observed. This confirmed that the number of Sb oxide particles in the p-type Bi-Te-based thermoelectric material can be reduced by adding zinc alone.

[0148] Fig.16 ] The temperature dependence of the thermal conductivity of the p-type thermoelectric material to which zinc oxide is added as a raw material and the p-type thermoelectric material to which zinc monomer is added as a raw material are shown in FIG. Fig.16 The horizontal axis represents absolute temperature (K), and the vertical axis represents thermal conductivity κ (WK -1 m -1 ).like Fig.16 As shown in Figure 2, when zinc oxide is added to the raw material, the thermal conductivity is almost not reduced. On the other hand, when zinc alone is added to the raw material, the thermal conductivity is reduced, and the number density of Sb oxide particles is 0 / mm 2 Similarly, the number density of Bi oxide particles is 0 particles / mm 2 In addition, when zinc oxide was added in its original state, it did not melt, and the distribution of zinc oxide particles was outside the scope of the present invention. From the above, it was confirmed that the performance of the thermoelectric material can be improved by adding zinc alone to the raw material and dissolving and solidifying it.

[0149] Fig.17 Graph (A) shows the ZnTe amount dependence of the dimensionless quality factor ZT of the n-type thermoelectric material 2 at around room temperature (325 K). Fig.17 The horizontal axis is the ZnTe content (at%), and the vertical axis is the dimensionless quality factor ZT. Fig.17 As shown, when y=2, it is higher than that when no ZnTe is added (y=0%).

[0150] Fig.18 The element distribution results of n-type thermoelectric material 2 are shown in FIG. Fig.18 As shown, Zn and O were detected in the confirmed particles, and the presence of a large amount of zinc oxide nanoparticles was confirmed.

[0151] Fig.19 Bi2 Se 0.3 Te 2.7 , lattice thermal conductivity κ of n-type thermoelectric material 3 and n-type thermoelectric material 4 lat temperature dependence. Fig.19 The horizontal axis is temperature (℃), Fig.19 The vertical axis is thermal conductivity κ (mW / (cm·K)). The lattice thermal conductivity of the sample with Al added tends to be lower than that of the sample without Al added. The Seebeck coefficient, resistivity, and thermal conductivity of these samples as a function of carrier concentration are greatly different, so the quality factor B is calculated as an indicator of performance that is not affected by carrier concentration. Fig. 20 The relationship between the quality factor B and the Al content is shown in FIG. Fig. 20 y=1 in the figure is the result of n-type thermoelectric material 4, and y=2 is the result of n-type thermoelectric material 3. Among the samples with Al added, the values ​​of the quality factor of the samples with y=1 and y=2 exceeded those of the samples without Al addition, especially in the direction perpendicular to the sintering direction.

[0152] Fig.21 Bi 0.45 Sb 1.55 Te 3 , temperature dependence of the dimensionless quality factor ZT of the p-type thermoelectric material 2 and the p-type thermoelectric material 3. Fig.21 The horizontal axis is temperature (K). The dimensionless quality factor ZT of the p-type thermoelectric material 3 is higher than that of Bi 0.45 Sb 1.55 Te 3 From the above, it can be confirmed that the performance of the thermoelectric material can be improved by adding Al monomer to the raw material and dissolving and solidifying it.

[0153] Industrial Applicability

[0154] The thermoelectric material of the embodiment has an excellent performance index and thus has excellent industrial applicability.

[0155] Explanation of symbols

[0156] S1...dissolving and solidifying step, S2...powder preparation step, S3...sintering step

Claims

1. A thermoelectric material having a matrix, wherein the matrix has a composition formula represented by A2B3, wherein A in the composition formula is one or more elements selected from Bi and Sb, and B in the composition formula is one or more elements selected from Te, Se and S, Precipitate at least one of the interior of the crystal grains of the matrix and the crystal grain boundaries of the matrix: Oxide particles containing one or more elements selected from Group C containing Zn, Nb, and Al; and Telluride particles comprising one or more elements selected from the group C, The major diameter of the oxide particles is 1 nm to 1000 nm. The short diameter of the oxide particles is 1 nm to 500 nm, The telluride particles have a major diameter of 0.4 μm to 40 μm, The short diameter of the telluride particles is 0.4 μm to 20 μm.

2. The thermoelectric material according to claim 1, wherein At least one of the oxide particles and the telluride particles includes at least Zn.

3. The thermoelectric material according to claim 1, wherein At least one of the oxide particles and the telluride particles includes at least Nb.

4. The thermoelectric material according to claim 1, wherein At least one of the oxide particles and the telluride particles includes at least Al.

5. The thermoelectric material according to claim 1 or 2, wherein: The number of the oxide particles is greater than the number of the telluride particles.

6. The thermoelectric material according to claim 1 or 2, wherein: The maximum number density of Sb oxide particles is 31.2 particles / μm 2 the following.

7. The thermoelectric material according to claim 1 or 2, wherein: The maximum number density of Bi oxide particles is 12.4 particles / mm 2 the following.

8. The thermoelectric material according to claim 1 or 2, wherein: The oxygen concentration is 100 ppm or more, and the number of the oxide particles is greater than the number of particles of the element of the group C alone.

9. The thermoelectric material according to claim 1 or 2, wherein: The oxygen concentration is 400 ppm or more, and the number of the oxide particles is greater than the number of particles of the element of the group C alone.

10. The thermoelectric material according to claim 1 or 2, wherein: The oxygen concentration is 1000 ppm or more, and the number of the oxide particles is greater than the number of particles of the element of the group C alone.

11. The thermoelectric material according to claim 1 or 2, wherein: The Zn content is 0.40 to 2.4 at%.

12. The thermoelectric material according to claim 1 or 2, wherein: The Al content is 1.99 to 3.97 at%.

13. A thermoelectric element using the thermoelectric material according to claim 1 or 2.

14. A thermoelectric module using the thermoelectric element according to claim 13.

15. A device using the thermoelectric module according to claim 14.

16. A method for producing a thermoelectric material according to claim 1, comprising: a dissolution and solidification step, in which the raw materials are dissolved and solidified to obtain a solidified product; a powder preparation step of obtaining a powder from the solidified product; and a sintering step, which sintered the powder, The raw materials contain: At least one element selected from Group A consisting of Bi and Sb; At least one element selected from Group B consisting of Te, Se and S; and at least one element selected from the group consisting of Zn, Nb and Al, At least a part of the elements selected from the group C in the raw material exists as a monomer.

17. The method for producing a thermoelectric material according to claim 16, wherein: In the powder preparation step, the solidified product is pulverized in air.

Citation Information

Patent Citations

  • Thermoelectric material

    JP2014022731A

  • Processing apparatus and processing method

    JP2022104443A